A Cormac McCarthy Companion : The Border Trilogy - Arnold, Edwin T. (Book collections on Project MUSE., 2001)
With essays by Edwin T. Arnold, J. Douglas Canfield, Christine Chollier, George Guillemin, Dianne C. Luce, Jacqueline Scoones, Phillip A. Snyder, Nell Sullivan, and John Wegner The completion of Cormac McCarthy's Border Trilogy--All the Pretty Horses (1992), The Crossing (1994), and Cities of the Plain (1998)--marked a major achievement in American literature. Only ten years earlier this now internationally acclaimed novelist had been called the best unknown writer in America. The trilogy is McCarthy's most ambitious project yet, composed at the height of his mature powers over a period o.